2022
DOI: 10.1038/s41598-022-09590-2
|View full text |Cite
|
Sign up to set email alerts
|

Systematically evaluating DOTATATE and FDG as PET immuno-imaging tracers of cardiovascular inflammation

Abstract: In recent years, cardiovascular immuno-imaging by positron emission tomography (PET) has undergone tremendous progress in preclinical settings. Clinically, two approved PET tracers hold great potential for inflammation imaging in cardiovascular patients, namely FDG and DOTATATE. While the former is a widely applied metabolic tracer, DOTATATE is a relatively new PET tracer targeting the somatostatin receptor 2 (SST2). In the current study, we performed a detailed, head-to-head comparison of DOTATATE-based radio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 49 publications
0
10
1
Order By: Relevance
“… 2 The mechanism of 64 Cu-DOTATATE binding to SST 2 receptors expressed by inflammatory macrophages within recently infarcted myocardial tissue has been shown in a mouse model, using a combination of in vivo PET/CT imaging and ex vivo radiometric and immunologic assays. 4 In that study, 64 Cu-DOTATATE uptake within cell-sorted macrophages from infarcted mouse myocardium was 3-fold higher than 18 F-FDG.…”
mentioning
confidence: 79%
“… 2 The mechanism of 64 Cu-DOTATATE binding to SST 2 receptors expressed by inflammatory macrophages within recently infarcted myocardial tissue has been shown in a mouse model, using a combination of in vivo PET/CT imaging and ex vivo radiometric and immunologic assays. 4 In that study, 64 Cu-DOTATATE uptake within cell-sorted macrophages from infarcted mouse myocardium was 3-fold higher than 18 F-FDG.…”
mentioning
confidence: 79%
“…68 Ga-DOTATATE targets more specifically the somatostatin receptor subtype-2 but is limited by its inability to distinguish beneficial from harmful inflammation. 49,50 Alternatively, ultra-small superparamagnetic iron oxide (USPIO), a clinically approved MRI contrast agent, can track and characterize macrophage-infiltration. 51,52 However, unlike Gd-based MRI agents that can be imaged within 1 h of administration, the typically 12-24 h time gap between pre-and postcontrast injection MRI acquisitions required for USPIO is impractical clinically and may preclude the possibility of short-term follow-up with other diagnostic MRI sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a retrospective study has found a strong correlation between CFs activation volume with cardiac function and peak creatine kinase via 68Ga-FAP-α inhibitor positron-emission tomography (PET) ( Kessler et al, 2021 ), while PET and single-photon emission computed tomography (SPECT) indirectly assessed cardiac fibrosis via myocardial perfusion imaging ( Gupta et al, 2021 ). PET immunoimaging DOTATATE tracers can find high expression of somatostatin receptor two in M1 inflammatory macrophages ( Toner et al, 2022 ). Multiparametric imaging characterizes the immune response transforming to tissue repair after MI ( Hess et al, 2022 ).…”
Section: Evaluations Of Cardiac Fibrosismentioning
confidence: 99%